A Time-Series Analysis of Building Footprint Data in a Shrinking City. - Tu, Jingyu. (2017)
Abstract: This thesis uses the building footprint data in a typical shrinking city, Baltimore, in 1972 and 2010 to achieve two prime research objectives. The first is to understand the historical patterns of housing construction and demolition in row house neighborhoods in Baltimore. And the second is to figure out the building footprint changes from 1972 to 2010, and the relationships between the change and some socioeconomic and physical factors. The conclusion is that the study area of five row house neighborhoods has experienced housing loss, but the conditions are different between the five neighborhoods. The housing loss is more likely to happen in areas with certain socioeconomic and physical characteristics, which can be explained by the unique construction and block patterns of row houses. On the basis of the research conclusion, the thesis came up with four policy recommendations for the City of Baltimore as the row house redevelopment strategies.; Thesis (M.A.)--Tufts University, 2015.; Submitted to the Dept. of Urban and Environmental Policy and Planning.; Advisor: Justin Hollander.; Committee: Barbara Parmenter.; Keyword: Urban planning.